In vitro evaluation of fibrolytic enzymes to increase digestion of fibrous feedstuffs - Elwakeel, E.A.; Johnson, B.J.; Titgemeyer, Evan C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Fermentations were conducted to identify enzyme activities and amounts that would optimize digestion of high-fiber feed ingredients (soybean hulls, alfalfa, corn silage, and corn gluten feed). In general, adding enzymes increased in vitro dry matter disappearance, but total volatile fatty acid concentrations were not improved by enzyme treatments. The response to enzymes was similar across substrate, suggesting that substrate specificity of the enzymes is not important. The most effective enzyme preparation had greater cellulase activity than the other enzyme preparations, suggesting that cellulase might be the most important enzymatic activity for improving digestion of fibrous feedstuffs.
Keywords: Beef; In vitro; Fibrolytic enzymes; Feedstuffs